2024
DOI: 10.1002/ecs2.4770
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the drivers of large herbivore distribution in human‐dominated southern African savannas

Dionísio V. Roque,
Thomas Göttert,
Ulrich Zeller
et al.

Abstract: African savanna ecosystems are home to the world's richest large herbivore (LH) assemblages. However, its landscapes are changing faster than any other region on Earth due to human activities and natural events. Therefore, understanding the factors influencing the distribution of LH in these human‐dominated environments is crucial for decision‐making on wildlife and habitat management. We combined ecological aerial surveys, camera trap, and dung count data to investigate how ecological (habitat types, perennia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…We often think about human presence in general, and urbanization in particular, as affecting ecological processes and having negative conservation impacts [19]. For example, Roque et al (2024) showed that even relatively sparse human settlements had strong negative effects on the presence of large herbivores in the Limpopo National Park in Mozambique [20]. In non-urban settings, rapid evolution can stem from limited anthropogenic change [21,22].…”
Section: Urbanization As An Ecological Phenomenon and A Conservation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…We often think about human presence in general, and urbanization in particular, as affecting ecological processes and having negative conservation impacts [19]. For example, Roque et al (2024) showed that even relatively sparse human settlements had strong negative effects on the presence of large herbivores in the Limpopo National Park in Mozambique [20]. In non-urban settings, rapid evolution can stem from limited anthropogenic change [21,22].…”
Section: Urbanization As An Ecological Phenomenon and A Conservation ...mentioning
confidence: 99%
“…In the more human-crowded urban setting, McDonald et al (2020) reviewed almost 1000 studies of ecological impacts [16]. Many species simply avoid areas where humans are present [23] or modify their behavior to allow coexistence [24,25], but some taxa are actually attracted to anthropogenic influences [20]. For plants, urbanization can decrease the availability of needed pollinators [26].…”
Section: Urbanization As An Ecological Phenomenon and A Conservation ...mentioning
confidence: 99%